2015
DOI: 10.1055/s-0034-1396313
|View full text |Cite
|
Sign up to set email alerts
|

Prospects of Boswellic Acids as Potential Pharmaceutics

Abstract: Boswellia serrata l " Burseraceae l " boswellic acids l " derivatization l " pharmacokinetics l " analysis methods l " new formula

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(40 citation statements)
references
References 90 publications
0
39
0
1
Order By: Relevance
“…Furthermore, AKBA failed to inhibit 5-LO product formation in human whole blood, showing activity only in enzyme assays [19]. In addition, recent research revealed little relevance for 5-LO in the inflammatory response associated with osteoarthritis, the major clinical indication of Boswellia extracts [20,21]. All products included in this survey are sold as botanical dietary supplements and are not intended to diagnose, treat, cure, or prevent any disease.…”
mentioning
confidence: 97%
“…Furthermore, AKBA failed to inhibit 5-LO product formation in human whole blood, showing activity only in enzyme assays [19]. In addition, recent research revealed little relevance for 5-LO in the inflammatory response associated with osteoarthritis, the major clinical indication of Boswellia extracts [20,21]. All products included in this survey are sold as botanical dietary supplements and are not intended to diagnose, treat, cure, or prevent any disease.…”
mentioning
confidence: 97%
“…[143]. Moreover, the reputation of BAs as potential pharmaceutical candidates found support in numerous studies [145]. A search in the frame of the EC-funded PlantLIBRA project retrieved six human studies reporting positive effects of B. serrata on several biomarkers such as nitric oxide, malondialdehyde, leukotriene C4, metalloprotease-3, eosinophil counts, leucocyte infiltration, etc.…”
Section: Exemplary Herbs Of Encouraging Benefitsmentioning
confidence: 99%
“…Their common medicinal properties are recognized in the treatment of inflammatory conditions, some cancerous diseases, and wound healing in the traditional medicines of India, China, Rome, Greece, Babylon, and elsewhere 3 . In the course of our characterization studies of the anti-inflammatory constituents in the gum resins of frankincense and myrrh, several terpenoid constituents were found to inhibit nitric oxide production in lipopolysaccharide LPS -activated mouse peritoneal boswellic acids; BAs 28 , and cembrane-type diterpenes, incensol and related compounds incensols: ICs 6, 15, 25 , have been identified as major constituents and have been considered to be biomarkers of frankincense Fig. 1 .…”
Section: Introductionmentioning
confidence: 99%